2022
DOI: 10.4103/jehp.jehp_1802_21
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mobile phone fitness applications on the level of physical fitness and psychological well-being during covid-19

Abstract: BACKGROUND: The impact of Coronavirus Disease-19 on peoples’ life has become evident. Recently, sport activities are important in improving individual health and their well-being. The aim of this study is to investigate the effect of using mobile phone fitness applications on some characteristics of physical fitness and psychological well-being of female university students. MATERIALS AND METHODS: A descriptive study design was implemented using a survey which was adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Also, Erbas and Demirer [29] came to the conclusion that AR activities play a key role in students' learning by giving them the opportunity to observe and examine organisms and their structures, a task that is normally extremely difficult under traditional teaching conditions. Technology tools such as AR technology provide advantages as a support tool in the process of learning and teaching [46][47][48][49][50]. The positive significant result found in this study may also be attributed to the fact that AR technology is capable of facilitating students' learning and understanding of the material through the activities it provides.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Also, Erbas and Demirer [29] came to the conclusion that AR activities play a key role in students' learning by giving them the opportunity to observe and examine organisms and their structures, a task that is normally extremely difficult under traditional teaching conditions. Technology tools such as AR technology provide advantages as a support tool in the process of learning and teaching [46][47][48][49][50]. The positive significant result found in this study may also be attributed to the fact that AR technology is capable of facilitating students' learning and understanding of the material through the activities it provides.…”
Section: Discussionmentioning
confidence: 60%
“…The results showed that AR is effective in providing such students with real-life experiences, enhancing their eagerness and enthusiasm to learn, and boosting their level of readiness and interest in the subject. According to [7,[50][51][52][53][54][55], the use of technology tools and video-based instruction through AR is effective in improving problem-solving skills when dealing with mathematics, specifically for students who require special education. Real-life experiences are essential for students with special needs in order for them to learn and acquire basic skills and knowledge in the classroom, and this can be achieved through the use of AR.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of learning and teaching, students are being exposed to several teaching options and alternatives thanks to the rise and development of digital technology (Jdaitawi, 2019;Muhaidat et al, 2022;Rasheed et al, 2021;Soliman et al, 2022). In addition, such digital technology developments have led to…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the development of digital technology has made it possible to increase the range of learning alternatives, which has brought about innovations learning and teaching (Jdaitawi, 2019(Jdaitawi, , 2020a(Jdaitawi, , 2020bJdaitawi & Kan'an, 2022;Manzano-Leon et al, 2021;Muhaidat et al, 2022;Rasheed et al, 2021;Soliman et al, 2022). In special education, unique teaching and learning strategies are needed for the facilitation of learning and skills acquisition of individuals with special needs, including the acquisition of communication and behavioral skills (Baragash et al, 2019;Cifuentes et al, 2016;Jdaitawi & Kan'an, 2022;Jdaitawi et al, 2022aJdaitawi et al, , 2022bManzano-Leon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%